ZEB1 Inhibits LHβ Subunit Transcription When Overexpressed, but Is Dispensable for LH Synthesis in Mice - Schultz, Hailey; Zhou, Xiang; Alonso, Carlos Agustín Isidro; Ongaro, Luisina; Lin, Yeu Farn; Loka, Mary; Brabletz, Thomas; Brabletz, Simone; Stemmler, Marc P.; Boehm, Ulrich; Bernard, Daniel J. (Endocrinology, 2024)
Luteinizing hormone (LH), a heterodimeric glycoprotein produced by pituitary gonadotrope cells, regulates gonadal function. Hypothalamic gonadotropin-releasing hormone (GnRH) stimulates LH synthesis and secretion. GnRH induces LHβ subunit (Lhb) expression via the transcription factor, early growth response 1 (EGR1), acting on the Lhb promoter. In contrast, overexpression of zinc finger E-box binding homeobox 1 (ZEB1) represses LH production in mice, but the underlying mechanism was not previously elucidated. Here, we observed that ZEB1 inhibited GnRH-stimulated but not basal Lhb mRNA expression in homologous murine LβT2 cells. Moreover, ZEB1 blocked GnRH and/or EGR1 induction of murine Lhb but not human LHB promoter-reporter activity in these cells. Using chimeric reporters, we mapped the species-specific ZEB1 sensitivity to sequence differences, including in Z- and E-boxes, in the proximal Lhb/LHB promoters, immediately upstream of the transcription start sites. ZEB1 bound to the murine Lhb promoter with higher affinity than to the human LHB promoter in this region. To examine ZEB1's physiological role in LH synthesis, we characterized gonadotrope-specific Zeb1 knockout mice. Loss of ZEB1 in gonadotropes did not affect LH production or secretion. Collectively, the data suggest that ZEB1, when overexpressed, can inhibit GnRH/EGR1 induction of murine Lhb transcription but does not play a necessary role in LH synthesis in mice.
CRIS-Team Scopus Importer:2024-10-11
Keywords: gonadotrope; knockout; pituitary; transcription; ZEB1